Pendampingan Pengembangan Brand Identity UMKM Berbasis Design Thinking untuk Meningkatkan Daya Saing Digital di Wilayah Klipang, Semarang - Lubertus Wahyu Prio Dwiantoro; Achmad Solechan; Hasan Aminda Syafrudin; Anna Erlina Christianti; Rina Dyah Wahyuningsih; Albertus Setyo Sumargo (Institut Teknologi dan Bisnis Semarang, 2026)
The development of the digital economy has intensified competition among Micro, Small, and Medium Enterprises (MSMEs), making the ability to establish a strong brand identity an essential factor in improving business competitiveness. However, many MSMEs in Klipang, Sendangmulyo Sub-district, Semarang City, still face challenges in developing professional visual identities, including limited knowledge of branding concepts, the absence of representative logos, and inconsistent application of visual elements in digital promotional media. This community service program aims to enhance the capacity of MSME actors in designing logos and developing brand identity through a Design Thinking approach as a strategy to strengthen business competitiveness in the digital economy era. The program was implemented using the Design Thinking framework, consisting of five stages: Empathize, Define, Ideate, Prototype, and Test. These stages were carried out through field observations, identification of MSME branding needs, brand concept exploration workshops, logo design training, brand story development assistance, and evaluation of visual identity implementation in digital promotional platforms. The target participants were 30 MSME actors in Klipang from various business sectors, including culinary, fashion, handicrafts, services, and trading. The results indicate that the Design Thinking approach successfully facilitated the development of structured visual identities for MSMEs through the creation of primary logos, alternative logos, monochrome versions, and transparent versions for each participant. Furthermore, the program improved participants’ understanding of brand identity, brand story development, and digital branding implementation to support marketing activities. The participatory process throughout the Design Thinking stages encouraged active involvement among MSME actors, resulting in brand identities that better represent the characteristics and values of their businesses. This community service activity demonstrates that Design Thinking can serve as an effective user-centered framework for MSME branding assistance, supporting the improvement of business readiness and competitiveness in the digital economy ecosystem.